On Stability of Solutions to Certain Differential Equations with Discontinuous Right-Hand Sides - Bezyaev, Vladimir Ivanovich (Eurasian Mathematical Journal, 2016)
For a class of nonlinear nonautonomous systems of differential equations with discontinuous right-hand sides effective conditions for stability and instability of their solutions are given.